PENGARUH MAKNA POSITIF DAN KETERLIBATAN KOGNITIF TERHADAP KOMITMEN ORGANISASI PADA KARYAWAN BUTIK PUSPITA KEBAYA SALATIGA - Nurwaningsih, Zulfia; Arenggoasih, Wuri (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2025)
This study aims to examine the influence of work meaningfulness and job involvement on organizational commitment among employees of Butik Puspita Kebaya Salatiga, both simultaneously and partially. A quantitative approach was employed using an explanatory survey method, involving the entire population of 36 employees through a saturated sampling technique. Data were collected using a Likert-scale questionnaire covering three main variables: organizational commitment, work meaningfulness, and job involvement. The results indicate that simultaneously, work meaningfulness and job involvement have a significant effect on organizational commitment, as evidenced by a significance value of 0.000 and an F-value of 121.941, which exceeds the F-table value of 3.28. Partially, work meaningfulness has a significant effect on organizational commitment with a significance value of 0.001 and a t-value of 3.793, greater than the t-table value of 2.03452. Similarly, job involvement also significantly influences organizational commitment, with a significance value of 0.011 and a t-value of 2.703, exceeding the t-table threshold. The coefficient of determination (R Square) is 0.881, indicating that 88.1% of the variation in organizational commitment is explained by work meaningfulness and job involvement, while the remaining 11.9% is influenced by other factors not included in this study